2022
DOI: 10.1038/s41893-022-00940-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Earth system interactions for sustainable food production via expert elicitation

Abstract: Several safe boundaries of critical Earth system processes have already been crossed due to human perturbations; not accounting for their interactions may further narrow the safe operating space for humanity. Using expert knowledge elicitation, we explored interactions among seven variables representing Earth system processes relevant to food production, identifying many interactions little explored in Earth system literature. We found that green water and land system change affect other Earth system processes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 84 publications
0
18
0
2
Order By: Relevance
“…Although we only visually investigated broad patterns of crop production (Figure 2, Figure 4), ignoring other key constraints such as market access or potential crop suitability 15 , this might indicate that there exist opportunities to sustainably intensify and manage foodscapes better in a regional and global context 83 . Potentially NBS, such as restoration, agroforestry or better soil, watershed and nutrient management can effectively address inter-related challenges to help humanity stay within its planet boundaries 84,85 . Overall, the concept and our initial mapping of foodscape can contribute towards identifying opportunities for agri-economic interventions and sustainable intensification, especially in areas with inefficient current production or with considerable risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we only visually investigated broad patterns of crop production (Figure 2, Figure 4), ignoring other key constraints such as market access or potential crop suitability 15 , this might indicate that there exist opportunities to sustainably intensify and manage foodscapes better in a regional and global context 83 . Potentially NBS, such as restoration, agroforestry or better soil, watershed and nutrient management can effectively address inter-related challenges to help humanity stay within its planet boundaries 84,85 . Overall, the concept and our initial mapping of foodscape can contribute towards identifying opportunities for agri-economic interventions and sustainable intensification, especially in areas with inefficient current production or with considerable risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial concentration of global food production in very few foodscape classes also results in considerable risks towards food security 86 as well as creating tensions with the achievement of other sustainable development goals such as clean water or life on land 84,87 . We also find that about ~40% of all foodscape classes are exposed to single or multiple pressures globally (Figure 5a), with particularly intensively cultivated foodscapes being more often affected by multiple rather than single pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysafi et al. (2022) investigated the interactions of food production‐related PBs and found that the green‐water PB can exert a strong influence on other PBs, while the blue‐water PB is highly influenced by other PBs. Therefore, future research should pay more attentions to this issue.…”
Section: Future Outlookmentioning
confidence: 99%
“…Root-zone soil moisture is now substantially modified by human activities, such as greenhouse gas emissions, deforestation, aerosol pollution, freshwater depletion, and their interactions (Chrysafi et al, 2022). These human modifications of root-zone soil moisture and the Earth system implications of its changes prompted the suggestion to include root-zone soil moisture in the planetary boundaries framework as the green water planetary boundary (Wang-Erlandsson et al, 2022).…”
mentioning
confidence: 99%